1999
DOI: 10.1080/03079459994380
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of four types of infectious bronchitis virus (793/B, 624/I, B1648 and Massachusetts)

Abstract: Eighteen isolates of infectious bronchitis virus (IBV) from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 17 publications
3
95
1
4
Order By: Relevance
“…Several studies (Lin et al, 1991;Kwon et al, 1993b;Keeler et al, 1998) have reported a high correlation between the genotype and serotype of strains, while other papers present conflicting data between the genotype and serotype and/or protectotype (Clewley et al, 1981;Kusters et al, 1987;Capua et al, 1998;Hein et al, 1998;Minta et al, 1998). Also, genotyping a strain by two different genotyping methods may result in contradictory results (Capua et al, 1998(Capua et al, , 1999.…”
Section: Genotypesmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies (Lin et al, 1991;Kwon et al, 1993b;Keeler et al, 1998) have reported a high correlation between the genotype and serotype of strains, while other papers present conflicting data between the genotype and serotype and/or protectotype (Clewley et al, 1981;Kusters et al, 1987;Capua et al, 1998;Hein et al, 1998;Minta et al, 1998). Also, genotyping a strain by two different genotyping methods may result in contradictory results (Capua et al, 1998(Capua et al, , 1999.…”
Section: Genotypesmentioning
confidence: 99%
“…There are several reports on serotyping by the HI test (Lashgari & Newman, 1984;Brown & Bracewell, 1985;Toro et al, 1987;Cook et al, 1987;Capua et al, 1998Capua et al, , 1999. Brown & Bracewell (1985) found high cross-reactions between serotypes in the HI test.…”
Section: Antigenic Typesmentioning
confidence: 99%
See 3 more Smart Citations